The Process of Learning English Speaking Skills - Qamili, Shpresë (European Journal of Multidisciplinary Studies, 2016)
Language gives people the opportunity to express their feelings, desires, thoughts and ideas. Language is a tool, whereby is discovered, acquired, transmitted, stored and inherited knowledge about the world and universe. Language is one of the most significant indicator of linguistics and cultural identity of the language community and individual personality. Language is the carrier of a culture, social behaviour and custom of the respective users. One of the four language skills in the process of learning English, is speaking skill as the first and main form of communication. It occupies a central place in the process of people enlightenment. Information is received, understood and easily processed through speaking or discourse than through writing. The speaking skills are donated to human beings in biological way. Speaking is a vital activity. Meanwhile, the language is a structural model of the system we use to convey our message while we are speaking. This study seeks to assess achievements and to determine the problem areas in the process of learning English speaking skills by high school students overall Kosova, suggesting appropriate recommendations for overcoming obstacles encountered. Thus, through it, are identified communication strategies that second-language learners use, whenever there are discovered linguistics deficiency, as well as difficulties in the process of learning verbal communication; interlinguistisc and intralinguistics communication strategies are revealed, that students use during oral communication, and their skills in the field of discourse are assessed